The hows and whys of face memory: level of construal influences the recognition of human faces - Wyer, Natalie A.; Hollins, Timothy J.; Pahl, Sabine; Roper, Jean (Frontiers in Psychology, 2015)
Three experiments investigated the influence of level of construal (i.e., the interpretation of actions in terms of their meaning or their details) on different stages of face memory. We employed a standard multiple-face recognition paradigm, with half of the faces inverted at test. Construal level was manipulated prior to recognition (Experiment 1), during encoding (Experiment 2) or both (Experiment 3). The results support a general advantage for high-level construal over low-level construal at both encoding and at recognition, and suggest that matching processing style between encoding and recognition has no advantage. We conclude with a discussion of implications for current theories relating to both construal and face processing.